Cost of Capital Revisited: Trends and Insights via Bibliometric Analysis and Literature Review - Gunawan, William Ben (Faculty of Economics and Business, Universitas Klabat, 2025)
This study explores the evolving landscape of cost of capital research through a bibliometric analysis and literature review. Examining publications from the Scopus database, the research identifies significant trends in scholarly output and country contributions over the past two decades. The bibliometric analysis reveals key thematic clusters, such as investment, risk, and capital structure, and highlights shifts in popular keywords over time. Concurrently, a comprehensive literature review synthesizes findings on the crucial importance of the cost of capital for business performance, sustainability, and competitive advantage. It also elucidates various strategies and solutions for its effective management and improvement. The study provides insights into the practical implications of optimizing the cost of capital for businesses and organizations, contributing to a holistic understanding of its role in financial decision-making.